Total and subcellular Ti distribution and detoxification processes in Pontoporia blainvillei and Steno bredanensis dolphins from Southeastern Brazil - Monteiro, Fernanda; Lemos, Leila S.; de Moura, Jailson Fulgêncio; Rocha, Rafael Christian Chávez; Moreira, Isabel; Di Beneditto, Ana Paula M.; Kehrig, Helena A.; Bordon, Isabella C. [UNESP]; Siciliano, Salvatore; Saint'Pierre, Tatiana D.; Hauser-Davis, Rachel Ann (Elsevier, 2020)
Titanium (Ti), used in many dailyuse products, such as shampoos and sunscreen filters, in the form of TiO2 nanoparticles (NPs), may elicit adverse marine biota effects. Marine mammal Ti data is scarce, and subcellular distribution and detoxification information is non-existent. Ti concentrations and metalloprotein detoxification in Pontoporia blainvillei and Steno bredanensis dolphins from Southeastern Brazil were assessed. Metallothionein (MT) concentrations were determined spectrophotometrically, total and subcellular Ti, by ICP-MS and detoxification, by HPLC-ICP-MS. Ti detoxification occurred through MT complexation. Statistical Ti-MT associations were observed in S. bredanensis liver, indicating TiO2 NPs contamination, as Ti binds to MT only as NPs. MT-Ti correlations were observed for both the coastal (P. blainvillei) and offshore (S. bredanensis) dolphins, evidencing oceanic TiO2 diffusion. Ti detoxification through binding to reduced glutathione occurred in both species. Thermostable subcellular fractions are a valuable tool for cetacean Ti detoxification assessments and should be applied to conservation efforts.
Keywords: Bioavailability; Delphinids; Detoxification; Metalloproteins; TiO2 nanoparticles; Titanium